Chinese accounting restatement and the timeliness of annual report. Issue 50 (27th October 2018) - Ma, Chen; Du, Hui; Zhang, Junrui
ABSTRACT: Chinese accounting restatements are mainly disclosed in companies' annual reports due to unique Chinese institutional background and regulatory setting. China provides the scheduled disclosure system for annual report, which is seldom found in any other countries. The difference between actual filing date and scheduled date as timeliness proxy can better depict how annual report is delayed by sudden events such as restatements. Using manually collected data of accounting restatements from 2004 to 2014, we study the association between Chinese accounting restatement and the timeliness of annual report. The results indicate that with an accounting restatement, a company takes longer to file annual reports than scheduled, suggesting a negative association between Chinese accounting restatements and timeliness of annual reports. We also find that this result is not altered whether CEO/chairman or auditor is the same between misstatement period and restatement period. The results are robust when other timeliness measures are used. When further examining the association between various restatement characteristics and timeliness of annual reports, we find an overall negative association between restatement severity and the timeliness of annual reports. We contribute to the existing accounting restatement literature from international perspective with evidence that restatements delay the timeliness of financial reporting.